Optimal Control For Malaria Epidemic Model With Vaccinating, Human Treatment And Mosquitos Spraying - Fahcruddin, Imam (2019)
In this paper we study the effect of vaccination control, medical treatment and spraying to malaria epidemic model.Firstly the non-control malaria epidemic model is generated and the equilibrium point is determined. Afterward, the stability of equilibrium point in previous model is investigated. The research is continued by deciding the optimal control of malaria epidemic model and minimizing the cost. The results show that the control effect can reduce the subpopulation of infected human and mosquitoes.